PEMANFAATAN RADIO DAN TV KOMUNITAS SEBAGAI MEDIA HUMAS LEMBAGA PENDIDIKAN - Rif'an, Ali (STAI Ma'had Aly Al-Hikam Malang, 2014)
Public relations (PR) in an educational institution has an important role in addition to the positive image of the institution as well as the massive media publicity. Radio and television are a media community that continues to develop according to the needs of the times. This paper describes how the use of radio and television as one of a medium of public relations education institutions associated with the policies within requirements of establishment, management, funding, and material. With some of those provisions, the role and utilization of radio and television can be maximized.